Innate immune cells in ischaemic heart disease: does myocardial infarction beget myocardial infarction? - Nahrendorf, Matthias (Eur Heart J, 2016)
Knowledge of macrophages in steady-state and diseased tissue is rapidly expanding, propelled by improved diagnostic capacity to detect and monitor cells in their native environments. In this review, we discuss implications for ischaemic heart disease and examine innate immune cell pathways that increase systemic leucocyte supply after myocardial infarction (MI). Acute MI alters the macrophage phenotype and supply chain from tissue resident to blood monocytes sourced from haematopoietic organs. That blood leucocytosis closely associates with cardiovascular mortality provides a strong motivation to understand why and how organ ischaemia alters cellular immunity.